THE ROLE OF SELF-REGULATORY AUDITING ASSOCIATIONS IN ARRANGEMENT OF AUDIT ACTIVITIES QUALITY CONTROL - Zinaida P. Arharova (Статистика и экономика, 2016)
The role of self-regulatory organizations in audit activities quality control is revealed in this article. Creation of a united audit association is the basis of certain regulating and auditing functions transfer from the government to the public sector.